Color Reflectance (Spectrophotometer) of IODP Hole 386-M0081E - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Color reflectance spectrophotometry and colorimetry data from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The data where obtained during the onshore phase of expedition 386 which took place between 2022-02-14 – 2022-03-15 onboard D/V Chikyu. After longitudinal splitting of the core sections, each archive half was scanned by the Tri-Sensor Core Logger (TSCL; NS Design) including a noncontact imaging spectrophotometer (MetaVue VS3200; X-Rite), recording data at 2-cm sampling interval. The obtained data is represented in the L*a*b* color coordinate system, where L* is a total reflectance index ranging 0%–100%, a* is green (<0) to red (>0) chromaticity, and b* is blue (<0) to yellow (>0) chromaticity. L*a*b* values were transferred into RGB values using the MATLAB routine lab2rgb. For further methodological information see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023